Transient absorption and anisotropy studies of a push-pull azo derivative with an isomerization path-selective local minimum in the ground state - Garcia, Rafael de Q.; Buckup, Tiago; Ishow, Éléna; De Boni, Leonardo (The journal of chemical physics, 2025)
The ultrafast excited-state dynamics of the E and Z isomers of a push-pull nitroazobenzene containing an octupolar bis(4′-tert-butylbiphenyl-4-yl)aminophenyl electron donor group were studied with transient absorption (TA) and TA anisotropy. A comprehensive study with two excitation wavelengths and a broadband white-light continuum probe (400-1400 nm) has determined that a torsional isomerization mechanism is the most probable for both isomers. This has shed light on the excited state behavior of the elusive push-pull Z isomer, which has its properties mostly predicted by simulations and systematically lacks experimental observations. Meanwhile, another unproductive relaxation pathway, associated with a symmetric bending motion, was found only for the E isomer. When relaxing through this pathway, the molecule encounters a potential barrier in the ground state, which requires significant structural reorganization before full relaxation. This local minimum can be more general than expected and may be behind unsolved issues in the literature of azobenzenes.
Online veröffentlicht: 27. März 2025
Gesehen am 22.10.2025